Psychological Maltreatment and Well-Being in Parent-Child Relationships: A Dyadic Longitudinal Study - Erdinc, Beste; Deniz, Mehmet Engin; Dindaroglu, Esin; Satici, Seydi Ahmet; Akyil, Yusuf (SPRINGER, 2025)
Childhood psychological maltreatment can affect family members also. Thus, both the individual's maltreatment and its effects on family members must be considered. The current study investigated the impact of psychological maltreatment on the well-being of adolescents and their parents, using a diadic longitudinal approach. Therefore, for the first time, the connections between these concepts were assessed in terms of their evolution throughout time as well as in an interpersonal setting. A total of 452 individuals, including 226 adolescents and their one parent, participated in the study. Longitudinal APIM (L-APIM), which is the longitudinal extension of the actor partner interdependence model (APIM), one of the dyadic analysis techniques, was applied to examine the relationships between concepts. According to results, psychological maltreatment was found to reduce both partner and actor well-being. In other words, actor effects demonstrated that psychological maltreatment of adolescents and their parents had a detrimental impact on their well-being. In partner effects, it has been shown that parents' mental well-being is negatively affected by adolescents' psychological maltreatment and positively affected by adolescents' subjective well-being. In addition, parents' psychological maltreatment has a negative effect on adolescents' subjective well-being and parents' mental well-being has a positive effect on adolescents' subjective well-being. These findings suggest that treatments are necessary to safeguard and enhance the mental health of those who were subjected to psychological maltreatment as children as well as their relatives. It is emphasized that the programs to be implemented should target contributions for family members in addition to individual focus.
Keywords: Psychological Maltreatment; Well-being; Dyadic Longitudinal Study; PARTNER INTERDEPENDENCE MODEL; INTERGENERATIONAL CONTINUITY; SOCIAL RELATIONSHIPS; ASSOCIATIONS; HEALTH; ABUSE; Psychiatry